Analisis Perbandingan Metode Just In Time dan Economic Order Quantity - Adi Santoso (Department Industrial Engineering, University of Muhammadiyah Malang, 2009)
UD Surabaya Rattan Industry as the middle scale of company is produced rattan chairs. This company is based on the job order to plan and develop the future company to its business strategy become mass production. In process production, the company always faces problems in the row material supply. If the row material supply is saved in long time period and there is bulking in storage it can make the rattans will be under level quality. The purpose of this research is giving information about the choosing methods of planning, controlling the row material supply with differ between Just in Time (JIT) method with Economic Order Quantity (EOQ) to minimize inventory value. The result of from chosen method for the planning of inventory control of raw material. Total Inventory Cost (TIC) which in it there are three element of it expense of that is expense of purchasing, expense of ordering, and also stock holding cost got TIC for the Method of Just in Time (JIT) period 13 to Rp233.129.629,71. While for the Method of Economic Order of Quantity (EOQ) at period 13 to Rp234,171,969.21. Calculation of Total Inventory Cost (TIC) as a whole ( period of time 1 year) by applying Method of Just In Time ( JIT) it can be seen Totalize Inventory Cost (TIC) Rp5,012,483,943.59 while by applying Economic Order of Quantity (EOQ) from Total of Inventory Cost (TIC) Rp518,088,399.86. Becoming method planning of inventory control the selected method of Just In Time (JIT) with thrift equal to Rp5,604,456.27.